Multiswarm Artificial Bee Colony algorithm based on spark cloud computing platform for medical image registration. (August 2020) - Wen, Tingxi; Liu, Haotian; Lin, Luxin; Wang, Bin; Hou, Jigong; Huang, Chuanbo; Pan, Ting; Du, Yu
Highlights: This paper proposes a multiswarm Artificial Bee Colony multi-objective optimization algorithm (MS-ABC) .The algorithm can be applied to accelerate the solution of complex problems on Spark platform. Compared with the traditional algorithm, the algorithm greatly improves the speed of data processing, especially in the situation of large amount of data and high complexity. The algorithm runs on the Spark platform to accelerate the solution of complex application problems. It has excellent performance in the medical image registration. Abstract: Background: Over the years, medical image registration has been widely used in various fields. However, different application characteristics, such as scale, computational complexity, and optimization goals, can cause problems. Therefore, developing an optimization algorithm based on clustering calculation is crucial. Method: To solve the aforementioned problem, a multiswarm artificial bee colony (MS-ABC) multi-objective optimization algorithm based on clustering calculation is proposed. This algorithm can accelerate the resolution of complex problems on the Spark platform. Experiments show that the algorithm can optimize certain conventional complex problems and perform medical image registration tests. Result: Results show that the MS-ABC algorithm demonstrates excellent performance in medical image registration tests. The optimization results of the MS-ABC algorithm for conventional problems are similar to those of existing algorithms; however, its performance is more time efficient for complex problems, especially when additional goals are needed. Conclusion: The MS-ABC algorithm is applied to the Spark platform to accelerate the resolution of complex application problems. It can solve the problem of traditional algorithms regarding long calculation time, especially in the case of highly complex and large amounts of data, which can substantially improve data-processing efficiency.